1993
DOI: 10.1083/jcb.121.3.679
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix contains insulin-like growth factor binding protein-5: potentiation of the effects of IGF-I.

Abstract: Abstract. Insulin-like growth factor binding proteins (IGFBPs) have been shown to serve as carrier proteins for the insulin-like growth factors (IGFs) and to modulate their biologic effects. Since extracellular matrix (ECM) has been shown to be a reservoir for IGF-I and IGF-U, we examined the ECM of cultured human fetal fibroblasts and found that IGFBP-5 was incorporated intact into ECM, while mostly inert proteolytic fragments were found in the medium. In contrast, two other forms of IGFBP that are secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
342
2
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(358 citation statements)
references
References 41 publications
9
342
2
1
Order By: Relevance
“…IGFBP-2, -3, -4 and -6 were detected in the unconcentrated medium after 3 days culture, and we therefore used the conditioned medium collected are 2 days culture in most of the experiments. Previous reports showed that human fibroblasts expressed IGFBP-5 mRNA in human fibroblasts [5], but Western blot failed to detect this species in the present study. This may be due to the preferential binding of IGFBP-5 to extracellular matrix.…”
Section: Resultscontrasting
confidence: 53%
“…IGFBP-2, -3, -4 and -6 were detected in the unconcentrated medium after 3 days culture, and we therefore used the conditioned medium collected are 2 days culture in most of the experiments. Previous reports showed that human fibroblasts expressed IGFBP-5 mRNA in human fibroblasts [5], but Western blot failed to detect this species in the present study. This may be due to the preferential binding of IGFBP-5 to extracellular matrix.…”
Section: Resultscontrasting
confidence: 53%
“…In contrast to IGFBP-3, IGFBP-5 is preferentially 1:1000, the second (anti-guinea pig, horse-radish peroxidase-conjubound to extracellular matrix in human fibroblast cultures gated, from Anawa, Wangen, Switzerland) at a dilution of 1:500. [11]. Intact IGFBP-5 associates with mouse bone matrix [12].…”
Section: Processing Of Culture Media Blot Analysis For Igfbps and Ramentioning
confidence: 99%
“…The inflammatory process underlying asthma results from a highly complex interaction of various cell types (3)(4)(5). In addition, ECM interacts with inflammatory cells (6), forms a reservoir for cytokines and growth factors (7,8), influences trafficking of cells (9), and activates granulocytes to increase mediator release and enhance their survival (10,11). Conversely, several inflammatory mediators have a known proliferative effect on airway smooth muscle (ASM) and induce the synthesis of ECM and growth factors in fibroblasts and epithelial cells (12,13).…”
mentioning
confidence: 99%